Aktywność inwestycyjna przedsiębiorstw rolniczych Pomorza Środkowego - Szafraniec-Siluta, Ewa; Strzelecka, Agnieszka; Zawadzka, Danuta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The aim of this study is to determine the scale and structure of the investment activity of Middle Pomerania agricultural enterprises. The analysis was based on the value of investment and gross fixed assets in enterprises employing more than 9 people. The study covered data published by the CSO (GUS). The analyzed companies represent the agricultural sector in the region of Middle Pomerania (the area of Zachodniopomorskie and Pomorskie Voivodships). The period of study covers the years 2002–2010. The study shows that the value of investments in Poland from 2002 to 2008, has grown steadily. From the moment of crisis in global markets investment dynamics decreased. In agricultural enterprises, contrary to others, there was an increase in investment outlays in 2010, compared to the previous period. The agricultural sector was characterized by the lowest share of investments. The participation of agricultural enterprises in the region of Middle Pomerania in investment spending of the surveyed companies was higher than the share of agricultural enterprises in Poland, reflecting the agricultural character of this area.